The quest to the uncharted lands - Johnson, Jaleigh (Delacorte Press, 2017)
"Stella's parents are on the first expedition to the uncharted lands of Solace, but Stella doesn't want to be left behind. Stowing away aboard the ship, she finds a mysterious boy who is also hiding, and he's keeping a very big secret. She must decide whether to trust him or risk the fate of the expedition"--